Ministry of Agriculture and Land Reclamation Ministerial Decree No. 764 of the Year 2013 = وزارة الزراعة واستصلاح الأراضى قرار وزارى رقم 764 لسنة 2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.